DEKONSTRUKSI RUANG PAMER: MEMBACA PRAKTIK PAMERAN SENI KONTEMPORER DI LUAR INSTITUSI FORMAL DENGAN METODE KRITIK SENI: Membaca Praktik Pameran Seni Kontemporer di Luar Institusi Formal dengan Metode Kritik Seni - Sang Padi; Martien Roos Nagara (Jurusan Seni Rupa ISBI Bandung, 2025)
This study examines contemporary art exhibitions in alternative spaces using an artc riticism approach combined with a descriptive method. The research focuses on how alternative spaces function as flexible, experimental, and community-based platforms that differ from the institutional neutrality of the white cube paradigm. Data were analyzed through four stages of criticism: description, analysis, interpretation, and evaluation. Case studies of Pameran Antara Kota at Galeri Tjap Sahabat Bandung and Pameran Distribusi Distorsi at Abraham and Smith Bandung demonstrate that alternative spaces enable contemporary artists to negotiate ideas, create audience-oriented aesthetic experiences, and distribute artistic discourse beyond the logic of the mainstream art market. The findings conclude that alternative spaces are not merely sites of display but cultural strategies that sustain contemporary art ecosystems through accessibility, participation, and curatorial freedom.